Penerapan Pembiasaan Positif Dalam Upaya Peningkatan Karakter Anak Usia Dini - Veni Bara Lay; Josimoni Rilina Leba; Yoban Nicanor Marwanto Daud; Maya Sri Tapenu; Deby Suriyani Manimau; Fredericksen Victoranto Amseke (FKIP UNSULTRA, 2026)
Character education is an important aspect in early childhood development. The aim of this research is to determine the effect of implementing positive habits on improving the character of children aged 5-6 years. The method in this research is quantitative with an ex-post facto type. The sampling technique used a total sampling of 10 children aged 5-6 years at PAUD Efata Liliba, Kupang City. The data collection technique uses a questionnaire with the instruments of the Early Childhood Positive Habits Scale (based on Lickona, 2019 and Suyanto, 2020; reliability 0.812) and the Character Education Scale (based on Amseke, 2018; reliability 0.785). The data analysis technique is simple linear regression with SPSS 25.0. The results of these findings found that the application of positive habits had a positive and significant effect on improving the character of children aged 5-6 years (F=274.100; p=0.000; R Square=0.114), which means that positive habits contributed to character improvement of 11.4%. It is hoped that educators and parents can increase positive habits consistently through daily routines and singer activities at school and home to optimize the character of early childhood.